2022
DOI: 10.56093/ijas.v92i5.124628
|View full text |Cite
|
Sign up to set email alerts
|

Economically viable Mushroom (Pleurotus djamor) farming for nutritional security in Uttarakhand

Abstract: Pink oyster mushroom (Pleurotus djamor) owns a pleasant colour, good sensory attributes, high nutritional value, anti-oxidant, anti-microbial and medicinal properties. Cultivation of different types of mushroom has been accepted as a short-term income generating avenue under crop production for livelihood of the farmers. The present study was carried out to assess the nutritional quality, anti-oxidant activities and economic benefits of pink oyster mushroom at Research farm of G B Pant University of Agricultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…Considering P.djamor, a maximum of 32.55 ± 0.21 GAE mg g −1 for phenols was reported by Sasidhara et al 40 The flavonoid content of different Pleurotus species varies from 1.40 ± 0.52 to 29.80 ± 0.27 mg QE g −1 dry weight of extracts as per the records of Arbaayah and Umi. 41 The present study revealed that P.djamor contains 5.47 ± 0.13 mg QE g −1 flavonoids, which is higher than the data published by Nayak et al, 42 who reported 2.48 ± 0.04 mg QE g −1 . The RSA of aqueous extract of P.djamor was tested against DPPH.…”
Section: Anti-oxidants Potential Of Pdjamorcontrasting
confidence: 75%
“…Considering P.djamor, a maximum of 32.55 ± 0.21 GAE mg g −1 for phenols was reported by Sasidhara et al 40 The flavonoid content of different Pleurotus species varies from 1.40 ± 0.52 to 29.80 ± 0.27 mg QE g −1 dry weight of extracts as per the records of Arbaayah and Umi. 41 The present study revealed that P.djamor contains 5.47 ± 0.13 mg QE g −1 flavonoids, which is higher than the data published by Nayak et al, 42 who reported 2.48 ± 0.04 mg QE g −1 . The RSA of aqueous extract of P.djamor was tested against DPPH.…”
Section: Anti-oxidants Potential Of Pdjamorcontrasting
confidence: 75%
“…They also serve as excellent sources of polysaccharides, peptides, unsaturated fatty acids, tocopherols, ascorbic acid, terpenoids, phenolic compounds, nutraceuticals, antioxidants, and compounds with diverse health benefits, including anticancer, prebiotic, immune-modulating, anti-inflammatory, cardiovascular, antimicrobial, and antidiabetic properties. Numerous studies have highlighted mushrooms' remarkable array of beneficial compounds (Badalyan 2014;Rathore et al 2017;Gupta et al 2018;Kumar et al 2021;Nayak et al 2022).…”
Section: Introductionmentioning
confidence: 99%